ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS XI PADA MATERI BARISAN DAN DERET BERDASARKAN INDIKATOR KEMAMPUAN KOMUNIKASI MATEMATIS - Muzakir Zakir; Muhammad Jainuri; Awatif Awatif (Hiradika | Hira Institute, 2026)
Mathematical communication is essential for students to express, interpret, and represent mathematical ideas. This study aimed to describe grade XI students’ mathematical communication ability on sequences and series based on three communication indicators. A descriptive quantitative secondary analysis was conducted using 60 student score records available in the original research dataset. The instrument consisted of two open-ended problems on an arithmetic sequence and a geometric series; each response was scored on three indicators: expressing mathematical ideas in written/visual forms, understanding and evaluating mathematical ideas, and using mathematical terms, notation, and structures. Descriptive statistics and percentage achievement were calculated from item-level scores. The overall mean score was 7.30 out of 12 (60.83%). Indicator 1 reached 66.25%, indicator 2 reached 53.75%, and indicator 3 reached 62.50%. Performance on the second problem (69.72%) was higher than on the first problem (51.94%). The findings indicate that students’ main difficulty lies in understanding, interpreting, and evaluating mathematical ideas, particularly when generalizing a sequence pattern into a formal expression. Instruction should therefore provide more opportunities for students to explain reasoning, evaluate representations, and justify the use of symbols and formulas